2018
DOI: 10.1111/ijpo.12471
|View full text |Cite
|
Sign up to set email alerts
|

Associations between muscle mass, physical activity and dietary behaviour in adolescents

Abstract: Summary Background and objectives Investigations in older individuals suggest that adequate nutrition and physical activity are particularly important to skeletal muscle health; however, data in adolescents are scant and equivocal. The objective was to determine the associations among diet, physical activity and skeletal muscle mass in adolescents. Methods We assessed diet with four to seven 24‐h recalls and physical activity by accelerometry in 640 adolescents. Using total body measures of fat‐free soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The co-occurrence of high physical activity and high calorie-rich snacks and drinks consumption is consistent with a review in adults that reported exercise-induced increase in energy intake is typically compensated for by energy-dense food and drinks [ 33 ]. Consumption of calorie-rich snacks and sugary drinks may attenuate the beneficial effects of physical activity on skeletal mass [ 34 ] and the maintenance of body weight [ 33 ]. We also found that children of mothers with low educational level had higher odds of being allocated in the “physically active, high snacks and sugary drinks” cluster, but household income was not associated with being allocated to this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of high physical activity and high calorie-rich snacks and drinks consumption is consistent with a review in adults that reported exercise-induced increase in energy intake is typically compensated for by energy-dense food and drinks [ 33 ]. Consumption of calorie-rich snacks and sugary drinks may attenuate the beneficial effects of physical activity on skeletal mass [ 34 ] and the maintenance of body weight [ 33 ]. We also found that children of mothers with low educational level had higher odds of being allocated in the “physically active, high snacks and sugary drinks” cluster, but household income was not associated with being allocated to this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Our study con rms these trends and adds evidence to the amount of physical activity required. Hao et al reported an association between the skeletal muscle mass index (SMMI) and physical activity for 640 adolescents in short-term outcomes and suggested that SMMI was positively associated with physical activity 25 . However, there is limited knowledge regarding the association between skeletal muscle mass changes and the amount of physical activity for individuals aged 30-60.…”
Section: Discussionmentioning
confidence: 99%
“…Several hormonal factors like testosterone, growth hormone, and IGF-1, which are stimulated by physical activity, in turn, promote muscle mass accretion during adolescence ( 117 ). Recently, Hao et al ( 118 ) reported an association between moderate and vigorous physical activity with greater skeletal muscle mass in adolescents. On the contrary, they found that a diet rich in saturated fatty acids and sweetened soft drinks was associated with a lower muscle mass, also suggesting an attenuation of the beneficial effects of physical activity on muscle mass accretion during adolescence.…”
Section: Interventionsmentioning
confidence: 99%